2006
DOI: 10.1080/14786410500160942
|View full text |Cite
|
Sign up to set email alerts
|

Two new isoflavonoids fromBowdichia virgilioides

Abstract: Two new isoflavonoids 7,8,4'-trimethoxyisoflavone and 7,8,4'-trimethoxyisoflavanone and calycosin (7,3'-hydroxy-4'-methoxyisoflavone) were isolated from the wood of the leguminous tree Bowdichia virgilioides by usual chromatographic procedures. Besides these compounds the pterocarpane (-)-maackianin, isoliquiritigenin (4,2',4'-trihydroxychalcone), and the hydrobenzylfurane derivative bowdenol were also obtained. The structures of these new compounds were determinated by MS and 1D and 2D NMR spectral analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…6,7 Phytochemical studies carried out with some species belonging to this genus have demonstrated the occurrence of many classes of constituents, including terpenoids, flavonoids, and alkaloids. 8,9 According to the literature, chemical analysis revealed the presence of lupeol, sitosterol, stigmasterol, acosmine, ormosanine, and podopetaline in stem barks of B. virgilioides. 10,11 However, studies on the potential biological activity of B. virgilioides have not been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Phytochemical studies carried out with some species belonging to this genus have demonstrated the occurrence of many classes of constituents, including terpenoids, flavonoids, and alkaloids. 8,9 According to the literature, chemical analysis revealed the presence of lupeol, sitosterol, stigmasterol, acosmine, ormosanine, and podopetaline in stem barks of B. virgilioides. 10,11 However, studies on the potential biological activity of B. virgilioides have not been carried out so far.…”
Section: Introductionmentioning
confidence: 99%
“…Selective demethylation [18] of 6 e with AlCl 3 led to the corresponding 2’‐hydroxy‐isoflavone 6 j in 68 % yield, while a bromination of 6 c with NBS resulted in the 2’‐bromo‐isoflavone 6 k in 89 % yield. It is worth mentioning that six of the synthesized isoflavones are natural products ( 6 a , [19] 6 c , [20] 6 e , [21] 6 f , [22] 6 h , [23] 6 j [24] ).…”
Section: Resultsmentioning
confidence: 99%
“…48 The known derivatives 6,7,2 0 -trimethoxy-4 0 ,5 0methylenedioxyisoflavone, 6,7,3 0 ,4 0 -tetramethoxyisoflavone and 6,7,2 0 ,4 0 ,5 0 -pentamethoxyisoflavone co-occur with 1, but are less cytotoxic. 52 Maximaisoflavones M (5) and N (6) were isolated from extracts of the roots and aerial parts of Tephrosia maxima, respectively. 49 Acetone extracts of the roots of Dalbergia rubiginosa yielded 5-hydroxy-6,7-dimethoxy-3 0 ,4 0 -methylenedioxyisoflavone (2).…”
Section: Isoflavonesmentioning
confidence: 99%
“…52 Two isoflavanones (61,62) with an uncommon 5,7,2 0 ,3 0 ,4 0 -penta-O-substitution pattern have been isolated from 95% EtOH extracts of the aerial parts of Desmodium styracifolium, a species used in traditional Chinese medicine (see also [74][75][76][77]. 52 Two isoflavanones (61,62) with an uncommon 5,7,2 0 ,3 0 ,4 0 -penta-O-substitution pattern have been isolated from 95% EtOH extracts of the aerial parts of Desmodium styracifolium, a species used in traditional Chinese medicine (see also [74][75][76][77].…”
Section: Isoflavanonesmentioning
confidence: 99%